2014
DOI: 10.1111/bjd.12678
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofin vivoreflectance confocal microscopy on the number needed to treat melanoma in doubtful lesions

Abstract: Background The number needed to treat ratio is an effective method for measuring accuracy in melanoma detection. Dermoscopy reduces the number of false positives and subsequently unnecessary excisions. In vivo confocal microscopy is a non-invasive technique which allows the examination of the skin with cellular resolution. Objectives To assess the impact of RCM analysis on the number of equivocal lesions, assumed to be melanocytic, excised for every melanoma. Methods Consecutive patients (n=343) presenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
151
2
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(159 citation statements)
references
References 42 publications
3
151
2
3
Order By: Relevance
“…Reflectance confocal microscopy increases specificity in equivocal dermoscopic melanocytic lesions in two prospective studies [62]. This technology allows the diagnosis of subclinical lesions as amelanotic melanoma or better distinguishes the limits of the tumour [62], but has recently not been approved by NICE for routine use.…”
Section: Clinical and Dermoscopic Diagnosismentioning
confidence: 99%
“…Reflectance confocal microscopy increases specificity in equivocal dermoscopic melanocytic lesions in two prospective studies [62]. This technology allows the diagnosis of subclinical lesions as amelanotic melanoma or better distinguishes the limits of the tumour [62], but has recently not been approved by NICE for routine use.…”
Section: Clinical and Dermoscopic Diagnosismentioning
confidence: 99%
“…Recent longitudinal prospective studies demonstrated that the systematic application of RCM as a second-level examination in skin oncology influences the lesion outcome in two thirds of cases, improving diagnostic accuracy [8,9]. Although in these studies few false-negative results were found, the risk to miss confocal featureless melanomas should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Basal cell carcinomas have been diagnosed in vivo with 92−100% sensitivity and 97−85% specificity and melanomas with 92−88% sensitivity and 70−84% specificity (Guitera et al, 2012; Nori et al, 2004). Initial implementation in academic clinical settings (Alarcon et al, 2013; Pellacani et al, 2014) showed that RCM imaging combined with dermoscopy, reduced the number of unnecessary biopsies and thus also the economic burden associated with skin cancer management. This success has been achieved by a small cohort of “early adopter” clinicians, who, through working with the technology and performing the clinical studies, have become experts in reading RCM images.…”
Section: Introductionmentioning
confidence: 99%